The Identification of Rhizosphere Bacteria in Rumput Kebar from Kebar District, Tambrauw Regency: The Identification of Rhizosphere Bacteria in Kebar Grass from Kebar District, Tambrauw Regency - Rina A Mogea; Maria Massora; Yeni Salosa; Nurul Muzizah; Dian Kristin; Nuari Rante Tondok; Nurul Endang Lestari; Daniela Ijie (Jurnal Natural, 2023)
The area in the soil occupied by the part of the plant roots that interacts with microbes is generally known as the rhizosphere. Rumput Kebar (Biophytum umbraculum Welw), is a shrub that can be found in Kebar, Tambrauw Regency, West Papua. By the local community kebar grass is widely used as a reproductive medicine. The aim of this study was to isolate and characterize rhizosphere bacteria on rumput kebar. The bacteria were isolated from the rhizosphere of rumput kebar by serial dilution then grown in NA media and incubated for 48 hours. The growth of colony and cell shape were observed and biochemical tests were carried out. From the observations made, there were 6 isolates obtained, namely isolate RK 1 was of the genus Agromyces, RK 2 was the genus Acetobacterium, isolates RK 3, 4 and 7 were of the genus Lactobacillus, isolate 5 was of the genus Amphibacillus and isolate RK 6 was of the genus Cellulomonas. All of these bacteria play a role in absorbing water and nutrients, accelerating growth, as biocontrol, N2 fixation, antibiosis and symbiosis.